Factors associated with high viral load among HIV clients aged 15 years and older receiving treatment in Tanga city council, Tanzania: A facility-based cross-sectional study - Aqbara Ibrahim Chande; Novatus A. Tesha; Bruno Sunguya (PLoS ONE, 2026)
Background High viral load indicates poor treatment outcomes among people living with HIV (PLHIV) on antiretroviral therapy (ART). However, there is a dearth of evidence on specific factors associated with high viral load in resource-limited settings, including Tanzania. Aim The aim of this study is to identify factors contributing to high viral load among PLHIV aged 15 years and older on ART for at least six months in Tanga, Tanzania. Methods This is analytical cross-sectional study of 233 PLHIV attending the Care and Treatment Centre (CTC) in Tanga region from September to November 2023. A systematic sampling method was used to select participants for face-to-face interviews. A structured questionnaire was used to collect socio-demographic information while clinical data were collected from the patients’ records and CTC database. Descriptive analysis was used to estimate the prevalence of high viral load, while Pearson Chi-square tests compared categorical variables, and the logistic regression assessed determinants of high viral load. Results High viral load was prevalent among 35.2% [95% CI: 29.3%−41.6%] PLHIV attending CTC in Tanga region. Higher viral load was noted among younger adults (52.5%), those in sales/services (63.6%), professionals (54.5%), and unskilled workers (53.2%) compared to their counterparts. PLHIV with severe food insecurity were more likely to exhibit higher viral load compared to those from food secure households (AOR = 9.6; 95% CI: 2.6–35.2). Those consuming alcohol were 4.2 times more likely to have a higher viral load compared to non-drinkers (AOR = 4.2; 95% CI: 1.4–12.5). PLHIV aged 20–24 were 5.4 times more likely to exhibit elevated viral load levels compared to their older counterparts (AOR = 5.4; 95% CI: 1.8–15.7). Additionally, PLHIV in sales and services occupations were 6.1 times more likely to have a higher viral load compared to those in agriculture (AOR = 6.1; 95% CI: 1.1–35 and those facing high stigma were 4.3 times more likely to have a higher HVL than individuals with good social support and low stigma (AOR = 4.3, 95% CI: 1.0–18.7, p = 0.049).). Conclusion More than one in three adult PLHIV on ART in Tanga Tanzania had a high viral load. This burden highlights a steep climb to reach the last 95 target ahead of the deadline. Efforts should focus on young adults, those with households’ food insecurity, consuming alcohol, and with perceived stigma in Tanzania and areas with similar context.